The adoption, implementation and impact of IMF programs : a review of the issues and evidence - Joseph P. Joyce (Wellesley College, Department of Economics, 2003)
This paper evaluates the literature on the lending programs of the IMF. The first section deals with the initiation of a Fund program, which has been shown to be influenced by political and institutional variables. A second focus of research analyzes the design and implementation of Fund supported polices, since many programs are often not successfully completed. The third issue surveyed is the impact of IMF policies on the economy of the borrowing government. The effect of Fund programs on private capital flows is also examined. The last section presents issues that merit further research.
Keywords: O1; F3; 330; IMF programs; conditionality; Internationaler Kredit; Anpassungsprogramm des IWF; Entwicklungsländer